2017
DOI: 10.1097/wnr.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Left-lateralization of resting state functional connectivity between the presupplementary motor area and primary language areas

Abstract: An abundance of evidence points to a pre-supplementary motor area (pre-SMA) role in human language. This study explores the pre-SMA resting state connectivity network and the nature of its connections to known language areas. We tested the hypothesis that by seeding the pre-SMA, one would be able to establish language laterality to known cortical and sub-cortical language areas. We analyzed data from 30 right-handed healthy controls and performed the resting state functional MRI (rfMRI). A seed based analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…Intriguingly, the overall higher local activity we observed in the left compared to the right SMA—both in our dataset and in an independent sample from the HCP—implies that even though the placement of the magnet was symmetric, the baseline functional state of the SMA below the magnet was not. This baseline functional asymmetry is not totally unexpected, since stronger resting-state functional connectivity was previously observed with left compared to right seeds in both pre-SMA 101 and SMA proper 102 (but see ref. 103 ).…”
Section: Discussionsupporting
confidence: 68%
“…Intriguingly, the overall higher local activity we observed in the left compared to the right SMA—both in our dataset and in an independent sample from the HCP—implies that even though the placement of the magnet was symmetric, the baseline functional state of the SMA below the magnet was not. This baseline functional asymmetry is not totally unexpected, since stronger resting-state functional connectivity was previously observed with left compared to right seeds in both pre-SMA 101 and SMA proper 102 (but see ref. 103 ).…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies show seed‐based resting state fMRI lateralizes language function in healthy controls with moderate success (Joliot & Tzourio‐Mazoyer, 2016; Liu, Stufflebeam, Sepulcre, Hedden, & Buckner, 2009; Lou, Peck, Brennan, Mallela, & Holodny, 2017; Wang, Buckner, & Liu, 2014). Results in temporal lobe epilepsy have been inconsistent (Doucet, Pustina, et al, 2015; Teghipco, Hussain, & Tivarus, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at this time, we cannot determine hemispheric dominance with our current SBC rs-fMRI technique. We found a study by Lou et al [ 21 ] which demonstrated that seed placement over the bilateral pre-supplementary motor area (pre-SMA) allowed identification of left language lateralization in 30 right-handed healthy patients. We did not use the bilateral pre-SMA as a seed and may utilize this area for future seed placement.…”
Section: Discussionmentioning
confidence: 99%